Pengaruh Terapi Musik Instrumental Terhadap Intensitas Nyeri Persalinan Normal Kala I Fase Aktif - Siahaan, Gustin; Septiwiyarsi, Septiwiyarsi (Jurnal Kesehatan Bhakti Husada, 2022)
The pain experienced by mothers during the delivery process varies widely. Pain is caused by uterine contractions and cervical dilatation. The longer the pain that is felt will get stronger, the peak of pain occurs in the active phase. One of the methods used in pain control is the provision of music therapy. Music therapy is very effective for mothers who are about to give birth as an audionalgesic or sedative which can have a positive biomedical effect. This study aims to determine the effect of instrumental music therapy on the intensity of normal labor pain in the first stage of the active phase at PMB Saridah Jambi City in 2021.This research is a pre-experimental research with one group design. The population in the study is all mothers who will give birth based on the interpretation of childbirth in July-August 2021 at PMB Saridah Jambi City as many as 89 people. The sample in this study were23 people who were taken by purposive sampling technique. This research was conducted on August 2-25, 2021 at PMB Saridah, Jambi City. Collecting data using observation sheets. Data were analyzed univariately and bivariately using paired t test.The results showed that before being given instrumental music therapy most of the respondents had pain intensity in the severe category as many as 16 respondents (69,6%) and after being given most had pain intensity in the moderate category as many as 12 respondents (52.2%). There is an effect of instrumental music therapy on the intensity of normal labor pain in the first stage of the active phase with p = 0.000< 0.05.It is hoped that the results of this study can be used as positive input for handling labor pain with both pharmacological and non-pharmacological therapies such as instrumental music therapy.